MISCONCEPTION ANALYSIS OF STATIC ELECTRICITY MATERIALS IN CLASS IX JUNIOR HIGH SCHOOL - S C Octavia; A E Rahma; K Z Destine (ISER (Indonesian Science Education Research), 2021)
This study was made to determine the level of misconceptions of junior high school studentstowards static electricity and what are the obstacles for students in understanding the material sothat misconceptions occur. By using 7 students of SMPN 2 Hang Tuah Medan as research samples.The research method used is a qualitative method with a questionnaire technique with Gform andinterviews conducted online. By asking 5 questions about static electricity, it was found that about48.56% of the 7 students interviewed had misconceptions about static electricity. This happenedbecause of several factors, namely (1) the learning method was only in the form of explainingmaterial through group chats and independent study, (2) there was no evaluation conducted by theteacher on static electricity material. This is one of the limitations of online learning where theteacher focuses on explaining the material and does not provide opportunities for students to beinvolved in learning activities, resulting in the lack of self-confidence of students, and less than themaximum in achieving their knowledge.  For this reason, further action is needed by the teacher inorder to overcome the misconceptions of static electricity material that exist in students.